KAZA MITROVICA 1889–1900 (Heritage, 2021)
Kaza Mitrovica was part of the Priština Sandžak of the Kosovo vilayet until its liberation in the First Balkan War. The period from the opening of the consulate of the Kingdom of Serbia in Priština in 1889 until 1900 was marked by numerous murders and oppressions throughout Old Serbia, which did not skip Mitrovica. This situation deviated from the position of the city, which was located at the crossroads and at the end of the railway, whose starting point was Thessaloniki. In addition, Mitrovica was connected by road to neighboring towns, Novi Pazar, Peć and Priština, via Vučitrn. Thanks to that, it developed rapidly, the influx of inhabitants was higher and it represented the center of the northwestern part of the province of Kosovo.The newly arrived population in Mitrovica consisted of muhajirs fleeing Bosnia and Serbia, as well as Serbs who came from Metohija and other parts of Old Serbia due to violence. Also, numerous craftsmen and merchants settled in search of work and a better life. The city was the seat of a strong military garrison of the Turkish army, which did not react to prevent the tyranny of the Arbanas. On the contrary, the representatives of the civil and military authorities, in order to maintain an apparent peace, often negotiated with the greatest oppressors among the Arbanas.The relationship between the authorities and the villains was reflected on the Serb population of Mitrovica, which was exposed to various atrocities. The only help was provided by the consulate of the Kingdom of Serbia in Priština, while the representatives of the authorities, from local to district, usually remained silent. This attitude of the Turkish authorities towards the crimes led to general insecurity and unrest among Serbs, who emigrated in large numbers to Serbia.
Keywords: Serbs, Arbanas, Kaza Mitrovica, oppressors, criminals